EFFECT OF ZINC NANOPARTICLES ON WATER POLLUTION TREATMENT (British Journal of Global Ecology and Sustainable Development, 2022)
Due to concerns about rising demand and falling supplies, the world now faces a growing problem of enough clean water. Although there are already technologies in place to disinfect water, these technologies have drawbacks, most notably the production of disinfection byproducts, which has prompted research into alternate techniques. Zinc oxide has generated interest as an antibacterial agent since it is a crucial ingredient in the rubber and pharmaceutical sectors. Zinc oxide has demonstrated antibacterial qualities at the nanoscale, making it potentially excellent for a variety of applications. This review examines zinc oxide synthesis with a focus on the precipitation process, its antimicrobial characteristic and the variables impacting it, disinfection mechanisms, and the possible use of water disinfection.